Pain, Anger, and the Fear of Being Discovered Persist Long after the Disclosure of HIV Serostatus among Adolescents with Perinatal HIV in Rural Communities in South Africa - Yvonne Maseko; Sphiwe Madiba (MDPI AG, 2020)
Informing adolescents of their HIV serostatus forms part of their HIV care and is a critical step in the transition to adult clinical care services. This article describes the experiences of adolescents with perinatal HIV in regard to disclosure, and examines the impact disclosure has on their emotional health and behaviors. We used a qualitative design to conduct interviews with 21 adolescents aged 12-19 years recruited from a rural district in South Africa. NVivo 10 computer software was used for thematic analyses. All adolescents were aware of their HIV-serostatus. The findings show that delayed disclosure, was a one-time event, and was unplanned. Disclosure occurred at the clinic rather than the adolescent's home. For most adolescents, feelings of anger, pain, sadness, negative perceptions of self, internalized stigma, and denial persisted long after disclosure occurred. They lived in constant fear of having their serostatus being discovered, and they developed a sense of fear of self-disclosure. Their negative emotions undermined treatment adherence. In contrast, other adolescents that described disclosure as a positive event, had accepted their HIV status, and lived similar to other adolescents. The prolonged negative reactions underscore the importance of ongoing post-disclosure interventions for adolescents in rural settings where psychosocial support services are insufficient to address their emotional wellbeing.